Popliteal venous thrombosis in juvenile arthritis with Baker cysts: report of 3 cases - Schirg Eckart; Wermes Cornelia; Dressler Frank; Thon Angelika (BMC, 2008)
Abstract Three pediatric patients with different illnesses leading to knee arthritis and large Baker cysts and additional calf swelling are reported. Calf swelling was due to true popliteal venous thrombosis and not to the much more common cause of pseudothrombophlebitis. Careful ultrasound examination can differentiate these two causes of calf swelling. Even though all our patients had risk factors for thrombophilia, we do not recommend routine thrombophilia work-up for all arthritis patients in the absence of thrombosis.